Wykluczenie cyfrowe osób starszych a rozwój e-usług w administracji w Polsce .......... 87 - Cebera, Agata (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
DIGITAL EXCLUSION OF OLDER PEOPLE AND THE DEVELOPMENT OF E-SERVICES IN ADMINISTRATION IN POLANDThe study attempts to analyze the impact of the phenomenon of digital exclusion of older people on the development of public administration e-services, with the basic research goal being to determine the legal limits of normative regulations establishing the legal obligation to use e-administration services. The analysis is dogmatic and legal in nature, and the basic research method is the logical linguistic method, however, to the extent necessary, elements of the statistical method were also used, to update the need to confirm or deny the occurrence of certain legally relevant phenomena.